Pelaporan Aset Sumber Daya Alam dan Lingkungan (Natural Capital Accounting) - Delima Ramdani; Bonor Manullang; Ricky Agustian; Muhamad Rizki; Daryanto Hesti Wibowo (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to analyze the application of Natural Capital Accounting (NCA) as an environmental accounting approach that integrates economic and ecological values into organizational reporting systems, with a focus on its relevance to sustainable development practices in Indonesia. Empirically, this study examines data from the Central Statistics Agency's (BPS) System of Environmental-Economic Accounting (SEEA) for 2019–2023, which shows a decline in the value of environmental assets of 19 trillion rupiah amid a significant increase in the value of national economic assets. The results of the analysis show that reporting environmental assets through NCA has the potential to improve the transparency and accountability of development policies, but its implementation is still symbolic and does not fully capture the intrinsic value of ecosystems. In the context of legitimacy theory, NCA is seen as an important instrument for maintaining public trust in the sustainability performance of companies and the government, while critical accounting theory highlights that the process of monetary valuation of natural capital is still dominated by market logic and economic efficiency. This study concludes that reformulation of environmental accounting policy is necessary so that NCA does not merely become an administrative reporting tool, but also a strategic instrument in realizing ecological justice and a green economy in Indonesia.